The meridional and seasonal variability of the carbonate system in the Southeast Atlantic sector of the Southern Ocean: SCALE 2019 Experiment - Binase, Zanele (Department of Oceanography, 2023)
Unlike well-characterized regions that have emerging pH and carbonate data, distant areas like polar oceans remain seasonally undersampled. Consequently, there may be a significant gap in our understanding of biological implications of future ocean acidification (OA). This study seeks to examine the seawater state conditions of the carbonate system that are currently experienced by marine organisms that depend on pH and Aragonite saturation (ΩAr) for calcification. The main focus was on how the physical and carbonate characteristics are sensitive to seasonal variability in the S.E Atlantic sector of the Southern Ocean. We analyzed the temperature, salinity, Dissolved Inorganic Carbon (CT), alkalinity data (AT), pH and Omega (ΩAr) at the surface and in the upper 1000m. We then compared the seasonal meridional gradients in the surface layer and in the upper 1000m water column. The CT and AT were measured using a VINDTA instrument while pH and ΩAr were derived using the CO2SYS program. The initial hypothesis was that the southernmost part of the Southern Ocean would acidify more in winter than in spring. This was based on the idea that colder waters hold more CO2. However, we found remarkable results showing that the surface CT was consistently higher in spring than in winter, with mean seasonal differences ranging from 5.86-21.90µmol/kg although SST was consistently higher in spring than winter, with mean seasonal differences ranging from 0.67-2.12˚C within the ocean front boundaries. It was then hypothesized that the temperature, biological production and CO2 flux seasonal cycles may have been out of phase. Consistent with the CT gradient, the surface pH and ΩAr were ±0.05 units lower in the warmer waters of spring and comparatively higher in winter. The seasonal lag was seen even within the interior layers of the column. There were three main findings in this study: Firstly, since the biogeochemically controlled seasonal CO2 seasonal transition variability lagged the heat flux influence on SST, the expected winter and spring seasonal conditions for carbonate were not reflected in the timing of the winter and spring cruises. Secondly, we observed an uncoupling of pH and ΩAr surface meridional gradients. While pH had no significant meridional gradient trend apart from frontal variability, ΩAr followed the meridional trend that was driven by CT. This was due to the impact of the meridional temperature gradient on K2 that compensated for the impact of the CT gradient on the pH. Lastly, we found that the impact of the seasonal cycle of carbonate stretched down to 1000 m and it was attributed to physical processes. Our findings led us to infer that from a carbonate perspective, the winter cruise was in fact the tail end of autumn while the spring cruise was the tail end of winter.